UJI FITOKIMA DAN AKTIVITAS ANALGESIK EKSTRAK ETANOL TANAMAN KUCING-KUCINGAN (Acalypha indica L.) PADA TIKUS PUTIH BETINA GALUR WISTAR (Rattus norvegicus L) - Wemay, Miranti Aike; Fatimawali, Fatimawali; Wehantouw, Frenly (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACTThis research aims to determine the phytochemical compounds and testing the analgesiceffects of ethanol extract of kucing-kucingan plant (Acalypha indica Linn.). Phytochemicaltesting conducted according to Harbone methods and analgesic activity of rats reaction timeis determined based on the thermal response after giving the ethanol extract of A indica L.This study used 20 female Wistar rats were divided into a treatment group was given 0,035mg / kg extract of leaves, stems and roots, negative control receive aquadest and positivecontrol using aspirin. Reaction time data were analyzed using One Way ANOVA followed byDuncan's test multipe Range Test. The results showed that the ethanol extract of A.indica L.contains alkaloids and saponins in the extract while the third type of flavonoid and tanninfound only in leaf extracts. Testing the analgesic activity of ethanol extract A. indica L.showed that the leaf extract gave the highest reaction time of 3.16 seconds, and stem and rootextracts followed by 1.72 seconds and 2.85 seconds. Reaction time in rats given leaf extractA.indica L. did not give significantly different with aspirin group (P> 0:05).Keywords : Phytochemical testing, analgesic, ethanol extract of kucing-kucingan (A.indicaL.).ABSTRAKPenelitian ini bertujuan untuk mengetahui senyawa fitokimia dan menguji efek analgetik